Does Allyship Attend to Sovereignty? - Carlson-Manathara, Elizabeth (Canadian Social Work Review / Revue canadienne de service social)

(untitled) (Canadian Association for Social Work Education / Association canadienne pour la formation en travail social (CASWE-ACFTS), 2024)
Accountability to Indigenous theories of change entails asking, does allyship attend to Indigenous sovereignty? In exploring this question, I briefly examine critical perspectives on — and limitations of — allyship frameworks, the emergence of critical allyship, and literature and models that specifically address the structure of colonialism and of Indigenous – settler relationships. Afterwards, I describe learning through a collective research collaboration around the framework living in Indigenous sovereignty, which to my mind, best attends to Indigenous theories of change, and which I find to be a compelling way to consider and enact my anti-colonial and decolonial work in relationship with Indigenous Peoples and lands.